Statistical Analysis of Multisensory and Text-Derived Representations on Concept Learning - Wang, Yuwei; Zeng, Yi (Frontiers in Computational Neuroscience, 2022)
When learning concepts, cognitive psychology research has revealed that there are two types of concept representations in the human brain: language-derived codes and sensory-derived codes. For the objective of human-like artificial intelligence, we expect to provide multisensory and text-derived representations for concepts in AI systems. Psychologists and computer scientists have published lots of datasets for the two kinds of representations, but as far as we know, no systematic work exits to analyze them together. We do a statistical study on them in this work. We want to know if multisensory vectors and text-derived vectors reflect conceptual understanding and if they are complementary in terms of cognition. Four experiments are presented in this work, all focused on multisensory representations labeled by psychologists and text-derived representations generated by computer scientists for concept learning, and the results demonstrate that 1)for the same concept, both forms of representations can properly reflect the concept, but 2) the representational similarity analysis findings reveal that the two types of representations are significantly different, 3) as the concreteness of the concept grows larger, the multisensory representation of the concept becomes closer to human beings than the text-derived representation, and 4) we verified that combining the two improves the concept representation.